COMPARISON OF RADIOGRAPHY WRIST JOINT POSTERIOR ANTERIOR (PA) ULNAR DEVIATION CENTRAL RAY VARIATION FOR ASSESSING OS SCAPHOID - Sari, Oktavia Puspita; Marlindo, Syandra Edo; Heriansyah, Heriansyah (Faculty of Vocational Studies, Universitas Airlangga, 2019)
Background: The technique of examining the wrist joint to see abnormalities in the carpalia region, especially in the scaphoid os, there is a special technique, namely ulnar deviation with variations of the central ray 150 to 250 proximally. Purpose: To determine in which direction the light is to assess the optimal scaphoid anatomy. Method: data retrieval is done by shooting wrst joints with 15x and 25x proximaly rays. Result: The direction of the angular ray is 15 degrees of scapoid which is free from overlapping and more informative. Conclusion: The average value of the results of the questionnaire processing is obtained on the technique with 15o ray variation of 3.2733 with a value of 0.083.